Der Wertpapierprospekt: empirische Befunde zur Qualität der Risikoangaben bei Neuemissionen - Klaus Henselmann; Martin Klein; Christian Maier (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2009)
The paper analyzes the risk disclosure quality in the prospectus of IPOs in Germany between 2006 and 2008. Quality of risk information is measured as precision and comprehensibility. The relationship between risk disclosure quality and earnings power is tested.
Keywords: G18; G38; K22; M41; M42; 650; Risikoberichterstattung; Publizitätsgüte; WpPG; Wertpapierprospekt; Börsengang; IPO; risk reporting; disclosure quality; WpPG; prospectus; initial public offering; IPO; qualitative content analysis; semiotics; MaxQDA qualitative Inhaltsanalyse; Publizitätsverhalten; Semiotik; MaxQDA